Influence of the primary tumour location in patients undergoing surgery for colorectal liver metastases. Issue 1 (January 2018) - Dupré, Aurélien; Malik, Hassan Z.; Jones, Robert P.; Diaz-Nieto, Rafael; Fenwick, Stephen W.; Poston, Graeme J.
Abstract: Background: The prognosis of patients undergoing liver resection for colorectal liver metastases (CLM) seems to be altered when the primary tumour is right-sided. However, data are lacking and conflicting. We aimed to evaluate the influence of the primary tumour location on oncologic outcomes following such surgery. Methods: We retrospectively analysed prospectively collected data from 376 consecutive patients who underwent liver surgery for CLM between June 2010 and August 2015. We compared the outcomes of patients with right colon tumours and those with left colorectal tumours. The splenic flexure was used as the cut-off point to determine the anatomic primary site. Results: Among the 364 patients eligible, 74 (20.3%) had a right-sided primary tumour. These patients were older, had a poorer American Society of Anaesthesiologists status and had fewer node-positive primary tumours. The CLM characteristics were similar between both groups. Median PFS was not significantly different between the two groups at 9.9 months, as well as the pattern of recurrence. Median OS was shorter for patients with right-sided primary tumour (34.6 versus 45.3 months, p = 0.035). Similar results were observed when patients with rectal tumour were excluded from analysis (34.6 vs. 47.5 months, p = 0.007). Primary tumour site was an independent prognosis factor in multivariate analysis. Conclusion: Right-sided location of the primary tumour is associated with worse OS after surgery for CLM, but seems to have no influence on PFS, and on the pattern of recurrence.